Impact of low levels of silver, zinc and copper nanoparticles on bacterial removal and potential synergy in water treatment applications. Issue 5 (24th January 2023) - Alherek, May; Basu, Onita D
Abstract: BACKGROUND: Point‐of‐use filtration units often incorporate silver as a disinfection aid. However, system performance and robustness may be increased by considering co‐application of additional transition metal nanoparticles (NPs) to support treated water disinfection. In this paper, the use of silver (Ag), zinc (Zn) and copper (Cu) NPs as disinfectants within drinking water applications was explored. Disinfection efficiency against E. coli was investigated over 72 h in batch‐phase experiments using NP concentrations within or lower than drinking water limits. Concentration ranges of the NPs were from 0 to 200 μg L −1, reflecting typical concentration reports for Ag in similar applications. Samples were examined with respect to pH and two water types. The effect of co‐application of NPs was assessed for potential synergy using the Bliss model, which compares individual treatment performance to combined treatment results. RESULTS: Disinfection efficacy when applying NPs individually was Ag > Cu > Zn with, for instance, complete removal (≥3 log) of E. coli observed with 50 ppb Ag at 24 h, 1 log removal by Cu and no removal achieved with application of Zn. The Bliss model analysis demonstrated the co‐application of NPs resulted in synergistic behavior with the combinations. Zn‐containing combinations (Ag–Zn and Cu–Zn) were significantly more synergistic than the Ag–Cu combination. CONCLUSIONS: Low‐level (0–200 ppb) concentrations of Ag, Cu and Zn demonstrated effective bacterial control and disinfection for E. coli under various water quality scenarios. In particular, co‐application of transition metal NPs increased system robustness and synergy, demonstrating potential for disinfection with water treatment applications. © 2023 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).